The SpongeBob SquarePants movie [videorecording (Blu-Ray)] - Hillenburg, Stephen; Drymon, Derek; Hill, Tim (Director); Osborne, Kent, 1969-; Springer, Aaron; Tibbitt, Paul; Hasselhoff, David (Paramount, 2023)
There's trouble brewing in Bikini Bottom. Someone has stolen King Neptune's crown, and it looks like Mr. Krab, SpongeBob's boss, is the culprit. Even though SpongeBob's just been passed over for the promotion of his dreams - to manage the new Krusty Krab - SpongeBob stands by his boss. Along with his best friend Patrick, the two set out on a treacherous mission to Shell City to reclaim the crown and save Mr. Krab's life.